Quantum light sources based on deterministic microlenses structures with (111) In(Ga)As and AlInAs QDs. (March 2020) - Derebezov, I A; Haisler, V A; Haisler, A V; Dmitriev, D V; Toropov, A I; Rodt, S; Helversen, M von; de la Haye, C; Bounouar, S; Reitzenstein, S
Abstract: The results of the development and implementation of a single photon source based on a bottom semiconductor Bragg reflector, top deterministic GaAs microlens structures and a single (111) In(Ga)As QD are presented. The structure of the microcavity ensures effective pumping of a single (111) In(Ga)As QD and high emission output efficiency, a clear single – photon emission was detected with a second – order correlation function at zero delay g (2) (0) = 0.07. A system of QD's on the basis of AlX In1-X As/AlY Ga1-Y As solid solutions has been studied. The usage of broadband AlX In1-X As solid solutions as the basis of quantum dots makes it possible to expand considerably the spectral emission range into the short-wave region, including the wavelength region near 770 nm being of interest for the design of aerospace systems of quantum cryptography. The optical characteristics of single AlX In1-X As quantum dots grown according to the Stranski–Krastanov mechanism are studied by the cryogenic microphotoluminescence method.